Honningsøde Orfeus - Jensen, Jeppe Sinding (Religionsvidenskabeligt Tidsskrift, 1983)
As an example of the predominant trend in modern structuralist-influenced classical research on the myths of antiquity the interpretation of Marcel Detienne of the myth of “Honeyed Orpheus” found in the fourth Georgic of Virgil is reviewed in this survey-article, thereby demonstrating the usefulness of the structuralist approach. The occasion for this review is the publication in 1981 of a series of articles by the French structuralist historians and mythologists Detienne, Vidal-Naquet, Vernant and Gernet, where most of the articles have been made available, collected form various sources, and translated into English for the benefit of a large public. A short description of the method employed by Claude Lévi-Strauss in his work with myths is followed by examples of the critique that has been levelled against him. But the emphasis here is on the positive results gained by the insight into cultural contexts through the process of deciphering the archaic and classical myths that structural analysis can provide. But the conclusion remains that any attempt to read ancient myths must relate carefully to the philological and historical achievements of related disciplines to complement a full and exhaustive description of the semantic universes disclosed in the classical myths.